Danske virksomheders finansiering i et makroøkonomisk perspektiv - Christina Petersen; Lars Risbjerg (Danmarks Nationalbank, 2009)
– Access to finance and the financing terms are important for firms' in-vestments and thus the business cycle developments. Danish non-financial corporations to a large extent finance their non-financial investments internally e.g. via retained earnings. During a business cycle expansion the analysis indicates, that corporations firstly finance themselves internally. Hereafter more expensive exter-nal debt financing is applied as the possibilities for internal financing gradually are exhausted. The costs of equity financing are normally higher than debt financing. However, for listed companies the results are consistent with at pat-tern where equity financing precede debt financing during an eco-nomic expansion. This is related to the fact that the cost of equity financing tend to fall at times of a rising stock market as it is typically the case already in the early phase of a economic expansion. Non-financial corporations normally increase their short-term borrow-ing in the early phase of an economic downturn. For corporations as a whole other short-term borrowing is rising more than short-term borrowing in banks, while the substitution away from short-term bank loans to other short-term loans does not seem to apply for borrowing by listed companies. Compared with large enterprises small and medium-sized enter-prises have a larger share of debt in relation to their total balance and apply banks and mortgage-credit institutions relatively more.
Keywords: 330; Unternehmensfinanzierung; Kapitalstruktur; Dänemark